Peramalan Produksi Gula Indonesia dengan Model ARIMA(2,2,0) Serta Bagaimana Strategi Swasembada Gula Terjadi Pada tahun 2030 - Wigid Hariadi; Sulantari Sulantari; Adi Mustika (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
Indonesia is an agrarian country with the agricultural sector playing a vital role in meeting basic needs and boosting the social, economic, and trade sectors. One of the widely cultivated crops is sugar cane, which is the raw material for sugar. Sugar is a strategic commodity and plays a vital role in the economy and community food security. The demand for sugar is enormous, but sugar production is still unable to meet all of this demand. Indonesia continues to strive to achieve sugar self-sufficiency. Therefore, the author is interested in conducting research related to how to forecast Indonesian sugar production for 2025-2030 using the ARIMA method? And what strategies are there to achieve Indonesian sugar self-sufficiency in 2030? The results obtained are: forecasting Indonesian sugar production can be done using the ARIMA (2,2,0), with an Sun Square Residuals value of 0.210136. Indonesia's sugar production forecasts from 2025 to 2030 are: 2.497 million tons, 2.450 million tons, 2.601 million tons, 2.635 million tons, 2.646 million tons, and 2.755 million tons, respectively. To achieve sugar self-sufficiency in Indonesia by 2030, the Indonesian government needs to add 1.19 million hectares of new land for sugarcane farming.